Potent achiral agonists of the ghrelin (growth hormone secretagogue) receptor. Part I: Lead identification. - Heightman, T; Scott, J; Longley, M; Bordas, V; Dean, D; Elliott, R; Hutley, G; Witherington, J; Abberley, L; Passingham, B; Berlanga, M; de Los Frailes, M; et al. (2007)
High throughput screening combined with efficient datamining and parallel synthesis led to the discovery of a novel series of indolines showing potent in vitro ghrelin receptor agonist activity and acceleration of gastric emptying in rats.